The EEG Split Alpha Peak: Phenomenological Origins and Methodological Aspects of Detection and Evaluation - Olejarczyk, Elzbieta; Bogucki, Piotr; Sobieszek, Aleksander (Frontiers in Neuroscience, 2017)
Electroencephalographic (EEG) patterns were analyzed in a group of ambulatory patients who ranged widely in age and sex using spectral analysis as well as Directed Transfer Function, a method used to evaluate functional brain connectivity. We tested the impact of window size and choice of reference electrode on the identification of two or more peaks with close frequencies observed in the spectral power distribution, so called ‘split alpha’. Together with the connectivity analysis, examination of spatiotemporal maps that showed the distribution of amplitudes of EEG patterns allowed for better explanation of the mechanisms underlying the generation of split alpha peaks. It was demonstrated that the split alpha spectrum can be generated by two or more independent and interconnected alpha wave generators located in different regions of the cerebral cortex, but not necessarily in the occipital cortex. We also demonstrated the importance of appropriate reference electrode choice during signal recording. In addition, results obtained using the original data were compared with results obtained using re-referenced data, using average reference electrode and reference electrode standardization techniques.